Pharmacokinetics and Tolerability of a New Low Molecular Mass Heparin (RO-11) in Healthy Volunteers – A Dose-Finding Study within the Therapeutical Range - Falkon, Liliana; Bayés, Miriam M; Frontera, Guillem; Garí, Mercè; Barbanoj, Manel; Fontcuberta, Jordi (Thrombosis and Haemostasis, 1997)
This paper reports on the results of a Phase I, dose-finding study with a new low molecular mass heparin (LMMH) called RO-11. The study focused on pharmacokinetics, dose-effect relationship and on tolerability of three single subcutaneous (SC) doses within the therapeutical range. After the injection of 7,500, 9,000 and 12,500 anti-FXa IU, the anti-FXa effect peaked between 3-6 h and showed a dose-dependent response. The absorption and elimination were first-order processes and the long half-life (>5 h) kept constant after increasing doses. The compound was tolerated very well and no clinically relevant prolongation of APTT, prothrombin and thrombin clotting tests was observed. At the dose of 7,500 IU, which corresponded to 110 anti-FXa IU/Kg, RO-11 exerted anti-FXa effect for at least 18-20 h. We recommend using this dose in a single SC injection, to evaluate the efficacy and safety of RO-11 in the initial treatment of DVT or PE.